An atomic-level polishing solution for TC4 titanium alloy, a preparation method thereof and a polishing process

By leveraging the synergistic effects of rare earth abrasives, oxidants, complexing agents, and dispersants, combined with polishing fluid and polishing processes, the micron-level processing challenges of TC4 titanium alloy surfaces have been solved, achieving atomic-level planarization and efficient material removal. This technology is suitable for applications in aerospace, biomedicine, and precision optics.

CN123043531APending Publication Date: 2026-11-06DONGHUA UNIV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611160058.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing processing technologies cannot achieve atomic-level planarization of TC4 titanium alloys. Traditional polishing techniques are mostly limited to the micrometer level, which cannot meet the high-end requirements of semiconductors and micro/nano devices. Furthermore, they are prone to leaving microscopic roughness and damage layers, increasing the risk of optical scattering and medical infection.

Method used

An atomic-level polishing slurry containing rare earth abrasives, oxidants, complexing agents, dispersants, and pH adjusters is used. After being ultrasonically stirred and mixed, it reacts with the surface of TC4 titanium alloy to form a uniform and easily removable reaction layer. Combined with the polishing process, atomic-level planarization is achieved.

Benefits of technology

It effectively improves the polishability of TC4 titanium alloy surface, achieving an atomic-level roughness of less than 0.2 nm and a material removal rate of greater than 280 nm/min. Moreover, the process is simple, environmentally friendly, and meets the requirements of green manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123043531A_ABST
    Figure CN123043531A_ABST
Patent Text Reader

Abstract

This invention discloses an atomic-level polishing slurry for TC4 titanium alloy, its preparation method, and polishing process, belonging to the field of novel aerospace titanium alloy material preparation technology. The polishing slurry comprises rare earth abrasive particles, an oxidant, a complexing agent, a dispersant, a pH adjuster, and deionized water. The rare earth abrasive particles are used to achieve mechanical removal of micro-areas on the surface; the oxidant promotes the formation of an easily removable reaction layer on the TC4 titanium alloy surface; the complexing agent promotes the complexation and dissolution of surface oxidation products; the dispersant improves the stability of the polishing slurry system; and the pH adjuster regulates the acidity and alkalinity of the polishing slurry. This polishing slurry achieves atomic-level planarization of the material surface through the synergistic effect of chemical reaction and mechanical removal. Furthermore, the polishing slurry preparation process of this invention is simple, the operating conditions are mild, and it uses a water-based environmentally friendly system, exhibiting good operability, industrial application feasibility, and green manufacturing advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of novel aerospace titanium alloy material preparation technology, and in particular to an atomic-level polishing slurry for TC4 titanium alloy, its preparation method and polishing process. Background Technology

[0002] TC4 titanium alloy is a typical α+β type titanium alloy, widely used in aerospace, biomedical, precision mold making, and optical manufacturing due to its high specific strength, good corrosion resistance, excellent biocompatibility, and stable high-temperature performance. With the rapid development of semiconductors, precision optics, biomedicine, and high-end equipment manufacturing, the demand for atomically flattened titanium alloy surfaces is increasing. For example, in semiconductors and micro / nano devices, atomically flat surfaces improve thin film deposition uniformity, reduce interface defect density, and enhance bonding quality; in precision optical devices, atomically flat surfaces effectively reduce light scattering and wavefront distortion; and in medical implants and high-end friction pairs, ultra-smooth surfaces help improve wear resistance, reduce bacterial adhesion, and extend service life.

[0003] However, existing processing technologies have revealed many core problems when faced with these high-end demands: traditional polishing techniques are mostly limited to the micrometer level and cannot meet the stringent standards of atomic-level planarization for semiconductors and micro / nano devices; existing processes are prone to leaving micro-roughness and damage layers, which not only exacerbate optical scattering but also increase the risk of infection in medical implants and shorten device lifespan.

[0004] Therefore, further improving the polishing performance of titanium alloys based on traditional processing to obtain high-quality, atomically flat new aerospace titanium alloy materials has become an important foundation for promoting their application in higher-end and more precise fields. Summary of the Invention

[0005] The present invention provides a method to overcome the above-mentioned problems.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows: This invention provides an atomic-level polishing slurry for TC4 titanium alloy, comprising the following components by mass percentage: 5.0-8.0 wt.% rare earth abrasive particles, 1.0-4.0 wt.% oxidant, 0.5-3.0 wt.% complexing agent, 0.3-1.0 wt.% dispersant, 0.1-1.0 wt.% pH adjuster, and the balance being deionized water.

[0007] Furthermore, the rare earth abrasive particles are any one of cerium oxide, lanthanum oxide, and praseodymium oxide.

[0008] Furthermore, the oxidant is any one of hydrogen peroxide, sodium hypochlorite, and potassium permanganate.

[0009] Furthermore, the complexing agent is any one of tartaric acid, phytic acid, and sorbic acid.

[0010] Furthermore, the pH of the polishing solution is 5-6.

[0011] In another aspect, the present invention provides a method for preparing the atomic-level polishing slurry, characterized by comprising the following steps: S1: Add rare earth abrasive particles to deionized water at a mass ratio of 1:3~5 and stir ultrasonically to obtain abrasive particle suspension A; S2: Add the dispersant to deionized water at a mass ratio of 1:2~3 and stir ultrasonically to obtain dispersant solution B; S3: Add the complexing agent to deionized water at a mass ratio of 1:2~3 and stir ultrasonically to obtain complexing agent solution C; S4: Add the dispersant solution B and the complexing agent solution C to the abrasive suspension A in sequence, and stir ultrasonically to obtain a mixture D; S5: Dissolve the oxidant in deionized water at a mass ratio of 1:3~5 to obtain oxidant solution E, and slowly add the oxidant solution E to the mixture D, and stir ultrasonically to obtain mixture F; S6: Add the pH adjuster to the mixture F, stir ultrasonically, and adjust the pH of the system to 5-6 to obtain the premix G; S7: Add deionized water to the premixed solution G to the set total amount, and stir ultrasonically to obtain the atomic-level polishing solution for TC4 titanium alloy.

[0012] Furthermore, the ultrasonic stirring time in S1-S7 is 30~60 min, the ultrasonic frequency is 20~60 kHz, and the stirring speed is 200~600 rpm.

[0013] In another aspect, the present invention provides a polishing process for TC4 titanium alloy, wherein the atomic-level polishing liquid is used to perform surface polishing treatment on TC4 titanium alloy workpieces.

[0014] Furthermore, the polishing process involves a polishing pressure of 20-30 kPa, a polishing disc rotation speed of 50-80 rpm, a polishing fluid flow rate of 10-20 mL / min, and a polishing time of 30-60 min.

[0015] Furthermore, after polishing, the surface roughness Sa of the TC4 titanium alloy is less than 0.2 nm, and the material removal rate is greater than 280 nm / min.

[0016] The beneficial effects of this invention are: (1) The atomic-level polishing slurry for TC4 titanium alloy provided by the present invention can form a uniform and easily removable reaction layer on the surface of the workpiece through the synergistic effect of oxidant, complexing agent, rare earth abrasive, dispersant and pH adjuster, thereby effectively improving the polishability of the TC4 titanium alloy surface and achieving atomic-level roughness of the titanium alloy surface.

[0017] (2) The polishing liquid of the present invention is simple to prepare. Each component is dissolved and dispersed separately and then mixed. The process flow is clear, the operating conditions are mild, and it is easy to achieve stable preparation and repeated preparation. It has good operability and industrial application feasibility.

[0018] (3) The polishing liquid of the present invention preferably uses environmentally friendly components. The preparation process uses water as the dispersion medium to avoid the use of a large amount of organic solvents. It has the advantages of low pollution, low environmental burden and good safety, which meets the development needs of green manufacturing and clean production. Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 Optical photograph of titanium alloy surface after rough grinding with 3000-grit sandpaper; Figure 2 Surface roughness of titanium alloy after coarse grinding with 3000-grit sandpaper; Figure 3 Example 1: Optical photograph of the polished titanium alloy surface; Figure 4 Example 1: Surface roughness of titanium alloy after polishing; Figure 5 XPS analysis of rare earth abrasive cerium oxide before and after use. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] Example 1 An atomic-level polishing slurry for TC4 titanium alloy, its preparation method and polishing process.

[0023] One of the atomic-level polishing slurries for TC4 titanium alloys comprises, by mass percentage, the following components: 5.0 wt.% rare earth abrasive particles, 3.0 wt.% oxidant, 1.5 wt.% complexing agent, 0.5 wt.% dispersant, 0.2 wt.% pH adjuster, and the balance being deionized water.

[0024] The rare earth abrasive particles are preferably any one of cerium oxide, lanthanum oxide, and praseodymium oxide, specifically cerium oxide abrasive particles; The oxidant is preferably any one of hydrogen peroxide, sodium hypochlorite, and potassium permanganate, specifically hydrogen peroxide; The complexing agent is preferably any one of tartaric acid, phytic acid, and sorbic acid, specifically tartaric acid; The dispersant is preferably any one of polyvinylpyrrolidone, polyethylene glycol, and sodium alginate, specifically polyethylene glycol; The pH adjuster is preferably any one or two of sodium bicarbonate and sodium carbonate, specifically sodium bicarbonate.

[0025] The polishing slurry is prepared as follows: S1: Weigh 100 g of cerium oxide abrasive particles and add them to 400 mL of deionized water. Stir with ultrasonication to obtain abrasive particle suspension A. S2: Weigh 10 g of polyethylene glycol and add it to 25 mL of deionized water and stir ultrasonically to obtain dispersant solution B; S3: Weigh 30g of tartaric acid and add it to 70 mL of deionized water and stir ultrasonically to obtain complexing agent solution C; S4: Add the dispersant solution B and the complexing agent solution C to the abrasive suspension A in sequence, and stir ultrasonically to obtain a mixture D; S5: Measure 60 mL of hydrogen peroxide and add it to 240 mL of deionized water to obtain oxidant solution E. Slowly add the oxidant solution E to the mixture D and stir ultrasonically to obtain mixture F. S6: Add 4g of sodium bicarbonate to the mixture F and stir ultrasonically. At this time, the pH is 5.3, and the premixed solution G is obtained. S7: Add deionized water to the premixed solution G to a final volume of 2000 mL, and ultrasonically stir to obtain the atomic-level polishing slurry for TC4 titanium alloy. The ultrasonic stirring time is 50 min, the ultrasonic frequency is 30 kHz, and the stirring speed is 500 rpm.

[0026] The atomic-level polishing fluid was used to perform surface polishing on TC4 titanium alloy workpieces.

[0027] Before polishing, the TC4 titanium alloy sample was first rough-ground using 3000-grit sandpaper. The surface morphology and roughness after rough grinding are as follows: Figure 1 and Figure 2 As shown.

[0028] Experimental results show that after rough grinding of TC4 titanium alloy with 3000-grit sandpaper, the sample surface still exhibits obvious machining textures and unevenness. (Based on optical photographs...) Figure 1 As can be seen, the surface uniformity is poor. The three-dimensional surface roughness parameters measured in this study are: Sa is the arithmetic mean height, Sq is the root mean square height, and Sz is the maximum surface height, with corresponding values ​​of 90.579 nm, 106.864 nm, and 730.331 nm, respectively, further indicating that the overall surface roughness of the sample after rough grinding is relatively high.

[0029] During the polishing stage, polishing slurry was continuously supplied to the surface of the rough-ground sample. The polishing pressure was set to 25 kPa, the polishing disc rotation speed to 60 rpm, and the polishing slurry flow rate to 15 mL / min. Polishing was continued for 30 min. The surface morphology and roughness results of the polished sample are as follows: Figure 3 , Figure 4 As shown. From optical photographs ( Figure 3 As can be seen, the TC4 titanium alloy surface treated with this polishing solution is uniform and smooth, without obvious scratches or defects, and the surface quality is significantly improved. The measured three-dimensional roughness parameters Sa, Sq, and Sz are 0.122 nm, 0.166 nm, and 1.592 nm, respectively, which are approximately 99.87%, 99.84%, and 99.78% lower than the rough-ground surface. The calculated material removal rate (MRR) of this process is 327 nm / min. The above results indicate that this polishing solution and its supporting process can effectively remove the machining texture and surface damage layer generated by rough grinding, achieving near-atomic-level planarization of the TC4 titanium alloy surface. The formula for calculating the MRR is as follows:

[0030] In the formula, ρ is the density of Ti-6Al-4V (g / cm³). 3 Its value is 4.51; A is the surface area of ​​the polished surface of the material (cm²). 2 ); t is the polishing time (min).

[0031] Example 2 An atomic-level polishing slurry for TC4 titanium alloy, its preparation method and polishing process.

[0032] One of the atomic-level polishing slurries for TC4 titanium alloys comprises, by mass percentage, the following components: 5.0 wt.% praseodymium oxide abrasive particles, 2.0 wt.% sodium hypochlorite, 1.5 wt.% phytic acid, 1.0 wt.% polyvinylpyrrolidone, 0.2 wt.% sodium carbonate, with the balance being deionized water.

[0033] The polishing slurry is prepared as follows: S1: Weigh 100g of praseodymium oxide abrasive particles and add them to 400mL of deionized water. Stir with ultrasonication to obtain abrasive particle suspension A. S2: Weigh 20g of polyethylene glycol and add it to 40 mL of deionized water and stir ultrasonically to obtain dispersant solution B; S3: Weigh 30g of phytic acid and add it to 70 mL of deionized water. Stir with ultrasonication to obtain complexing agent solution C. S4: Add the dispersant solution B and the complexing agent solution C to the abrasive suspension A in sequence, and stir ultrasonically to obtain a mixture D; S5: Measure 40 mL of hydrogen peroxide and add it to 160 mL of deionized water to obtain oxidant solution E. Slowly add the oxidant solution E to the mixture D and stir ultrasonically to obtain mixture F. S6: Add 4g of sodium carbonate to the mixture F and stir ultrasonically. At this time, the pH is 5.5, and the premix G is obtained. S7: Add deionized water to the premixed solution G to a final volume of 2000 mL, and ultrasonically stir to obtain the atomic-level polishing slurry for TC4 titanium alloy. The ultrasonic stirring time is 50 min, the ultrasonic frequency is 30 kHz, and the stirring speed is 500 rpm.

[0034] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.192 nm, and the material removal rate was 301 nm / min.

[0035] Example 3 An atomic-level polishing slurry for TC4 titanium alloy, its preparation method and polishing process.

[0036] One of the atomic-level polishing slurries for TC4 titanium alloys comprises, by mass percentage, the following components: 5.0 wt.% lanthanum oxide abrasive particles, 3.0 wt.% hydrogen peroxide, 1.5 wt.% tartaric acid, 0.5 wt.% polyethylene glycol, 0.2 wt.% sodium bicarbonate, with the balance being deionized water.

[0037] The polishing slurry is prepared as follows: S1: Weigh 100g of cerium oxide abrasive particles and add them to 400mL of deionized water and stir ultrasonically to obtain abrasive particle suspension A; S2: Weigh 10g of polyethylene glycol and add it to 25 mL of deionized water and stir ultrasonically to obtain dispersant solution B; S3: Weigh 30g of tartaric acid and add it to 70 mL of deionized water and stir ultrasonically to obtain complexing agent solution C; S4: Add the dispersant solution B and the complexing agent solution C to the abrasive suspension A in sequence, and stir ultrasonically to obtain a mixture D; S5: Measure 60 mL of hydrogen peroxide and add it to 240 mL of deionized water to obtain oxidant solution E. Slowly add the oxidant solution E to the mixture D and stir ultrasonically to obtain mixture F. S6: Add 4g of sodium bicarbonate to the mixture F and stir ultrasonically. At this time, the pH is 5.3, and the premixed solution G is obtained. S7: Add deionized water to the premixed solution G to a final volume of 2000 mL, and ultrasonically stir to obtain the atomic-level polishing slurry for TC4 titanium alloy. The ultrasonic stirring time is 50 min, the ultrasonic frequency is 30 kHz, and the stirring speed is 500 rpm.

[0038] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.171 nm, and the material removal rate was 310 nm / min.

[0039] Comparative Example 1 The difference from Example 1 is that the mass percentage of cerium oxide abrasive particles in the polishing slurry was changed to 10.0 wt.%. The preparation method S1 of the polishing slurry was changed as follows: 200g of cerium oxide was weighed and added to 600mL of deionized water and ultrasonically stirred to obtain abrasive suspension A.

[0040] The remaining polishing fluid ratios and polishing parameters are the same as in Example 1.

[0041] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.459 nm, and the material removal rate was 299 nm / min.

[0042] Comparative Example 2 The difference from Example 1 is that the mass percentage of cerium oxide abrasive particles in the polishing slurry was changed to 2.0 wt.%. The preparation method S1 of the polishing slurry was changed as follows: 40g of cerium oxide was weighed and added to 160 mL of deionized water and ultrasonically stirred to obtain abrasive suspension A.

[0043] The remaining polishing fluid ratios and polishing parameters are the same as in Example 1.

[0044] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.847 nm, and the material removal rate was 121 nm / min.

[0045] Comparative Example 3 The difference from Example 1 is that the mass percentage of hydrogen peroxide in the polishing slurry was changed to 5.0 wt.%. The preparation method S5 of the polishing slurry is changed as follows: 100 mL of hydrogen peroxide is added to 400 mL of deionized water and ultrasonically stirred to obtain oxidant solution E. The oxidant solution E is then slowly added to the mixture D and ultrasonically stirred to obtain mixture F.

[0046] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.705 nm, and the material removal rate was 155 nm / min.

[0047] Comparative Example 4 The difference from Example 1 is that the mass percentage of hydrogen peroxide in the polishing slurry was changed to 0.5 wt.%. The preparation method S5 of the polishing slurry is changed as follows: 10 mL of hydrogen peroxide is added to 40 mL of deionized water and ultrasonically stirred to obtain oxidant solution E. The oxidant solution E is then slowly added to the mixture D and ultrasonically stirred to obtain mixture F.

[0048] The remaining polishing fluid ratios and polishing parameters are the same as in Example 1.

[0049] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.641 nm, and the material removal rate was 175 nm / min.

[0050] Comparative Example 5 The difference from Example 1 is that the mass percentage of tartaric acid in the polishing solution was changed to 5.0 wt.%. The preparation method S3 of the polishing slurry was changed as follows: 100g of tartaric acid was weighed and added to 250 mL of deionized water and ultrasonically stirred to obtain complexing agent solution C.

[0051] The remaining polishing fluid ratios and polishing parameters are the same as in Example 1.

[0052] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.901 nm, and the material removal rate was 189 nm / min.

[0053] Comparative Example 6 The difference from Example 1 is that the mass percentage of tartaric acid in the polishing solution was changed to 0.2 wt.%. The preparation method S3 of the polishing slurry was changed as follows: 4g of tartaric acid was weighed and added to 10 mL of deionized water and ultrasonically stirred to obtain complexing agent solution C.

[0054] The remaining polishing fluid ratios and polishing parameters are the same as in Example 1.

[0055] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.613 nm, and the material removal rate was 201 nm / min.

[0056] Comparative Example 7 The difference from Example 1 is that the mass percentage of polyethylene glycol in the polishing slurry was changed to 1.5 wt.%. The preparation method S2 of the polishing slurry was changed as follows: 30 g of polyethylene glycol was weighed and added to 60 mL of deionized water and ultrasonically stirred to obtain dispersant solution B.

[0057] The remaining polishing fluid ratios and polishing parameters are the same as in Example 1.

[0058] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.433 nm, and the material removal rate was 251 nm / min.

[0059] Comparative Example 8 The difference from Example 1 is that the mass percentage of polyethylene glycol in the polishing slurry was changed to 0.1 wt.%. The preparation method S2 of the polishing slurry was changed as follows: 2 g of polyethylene glycol was weighed and added to 5 mL of deionized water and ultrasonically stirred to obtain dispersant solution B.

[0060] The remaining polishing fluid ratios and polishing parameters are the same as in Example 1.

[0061] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.493 nm, and the material removal rate was 217 nm / min.

[0062] Comparative Example 9 The difference from Example 1 is that the mass percentage of sodium bicarbonate in the polishing solution was changed to 1.5 wt.%. The preparation method S6 of the polishing slurry is changed as follows: 30 g of sodium bicarbonate is added to the mixture F and ultrasonically stirred. At this time, the pH is 10.2, and a premixed solution G is obtained.

[0063] The remaining polishing fluid ratios and polishing parameters are the same as in Example 1.

[0064] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.543 nm, and the material removal rate was 166 nm / min.

[0065] Comparative Example 10 The difference from Example 1 is that the mass percentage of sodium bicarbonate in the polishing solution was changed to 0.05 wt.%. The preparation method S6 of the polishing slurry is changed as follows: 1 g of sodium bicarbonate is added to the mixture F and ultrasonically stirred. At this time, the pH is 3.5, and a premixed solution G is obtained.

[0066] The remaining polishing fluid ratios and polishing parameters are the same as in Example 1.

[0067] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.690 nm, and the material removal rate was 198 nm / min.

[0068] Comparative Example 11 The only difference from Example 1 is that the polishing pressure in the polishing process is changed to 40 kPa.

[0069] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing pressure. The surface roughness Sa after polishing was 0.707 nm, and the material removal rate was 211 nm / min.

[0070] Comparative Example 12 The only difference from Example 1 is that the flow rate of the polishing slurry in the polishing process is changed to 30 mL / min.

[0071] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.847 nm, and the material removal rate was 231 nm / min.

[0072] Comparative Example 13 The only difference from Example 1 is that the polishing disc rotation speed in the polishing process is changed to 100 rpm.

[0073] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.782 nm, and the material removal rate was 267 nm / min.

[0074] Comparative Example 14 The only difference from Example 1 is that the polishing time in the polishing process is changed to 60 min.

[0075] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.504 nm, and the material removal rate was 225 nm / min.

[0076] Comparative Example 15 Unlike Example 1, only the polishing pressure in the polishing process was changed to 10 kPa.

[0077] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.789 nm, and the material removal rate was 102 nm / min.

[0078] Comparative Example 16 The only difference from Example 1 is that the flow rate of the polishing slurry in the polishing process is changed to 5 mL / min.

[0079] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.693 nm, and the material removal rate was 147 nm / min.

[0080] Comparative Example 17 The only difference from Example 1 is that the polishing disc rotation speed in the polishing process is changed to 30 rpm.

[0081] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.216 nm, and the material removal rate was 221 nm / min.

[0082] Comparative Example 18 The only difference from Example 1 is that the polishing time in the polishing process is changed to 15 minutes.

[0083] The TC4 titanium alloy sample after rough grinding in Example 1 was polished using the aforementioned polishing solution. The surface roughness Sa after polishing was 0.388 nm, and the material removal rate was 286 nm / min.

[0084] As shown in Table 1 below, the results of Examples 1-3 and Comparative Examples 1-10 indicate that when the content of rare earth abrasive particles, oxidant, complexing agent, dispersant, and pH adjuster is too low or too high, the polishing effect of the polishing slurry is significantly reduced, making it difficult to achieve an atomic-level surface of less than 0.2 nm, and the material removal rate also decreases. The results of Examples 1-3 and Comparative Examples 11-18 also indicate that when the polishing pressure, polishing disc rotation speed, polishing slurry flow rate, and polishing time are too high or too low, the polishing effect is also significantly reduced.

[0085] Table 1. Statistical analysis of polishing results

[0086] In the polishing slurry of this invention, the main function of rare earth abrasive particles is to remove the surface material and oxides from the complexed titanium alloy surface after the reaction. For example... Figure 5 XPS spectra before and after polishing with cerium oxide abrasive were used. Compared to before polishing, the fine O1s spectrum of the cerium oxide abrasive after polishing showed that, in addition to the inherent Ce-O structure of cerium oxide, a Ce-O-Ti structure also existed. As the cerium oxide abrasive particles moved, the titanium atoms in the Ce-O-Ti structure were complexed and removed, improving the material removal rate. This also indicates that rare earth abrasive particles not only have a mechanical effect but can also react with the surface to a certain extent to achieve complexation removal.

[0087] Oxidizing agents are used to form an oxide layer on the surface of titanium alloys. The specific reaction equation is as follows:

[0088]

[0089]

[0090] Complexing agents are used to promote the complexation and dissolution of the surface reaction layer. Taking tartaric acid as an example, tartrate ions complex Ti ions, weakening the mechanical properties of the oxide layer and improving the mechanical removal effect of rare earth abrasive particles. The specific equation is as follows:

[0091]

[0092] Dispersants are used to improve the stability of the polishing slurry system and inhibit abrasive particle agglomeration and sedimentation; pH adjusters are used to adjust the acidity and alkalinity of the polishing slurry and control the reactivity. Through the synergistic effect of the above components, the polishing slurry forms a controllable chemical softening layer on the TC4 titanium alloy surface, and stable removal is achieved by means of the micro-regional mechanical action of rare earth abrasive particles, thereby achieving the purpose of atomic-level planarization.

[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An atomic-level polishing slurry for TC4 titanium alloy, characterized in that, By mass percentage, it comprises the following components: rare earth abrasive particles 5.0~8.0 wt.%, oxidant 1.0~4.0 wt.%, complexing agent 0.5~3.0 wt.%, dispersant 0.3~1.0 wt.%, pH adjuster 0.1~1.0 wt.%, and the balance being deionized water.

2. The atomic-level polishing slurry for TC4 titanium alloy according to claim 1, characterized in that, The rare earth abrasive particles are any one of cerium oxide, lanthanum oxide, and praseodymium oxide.

3. The atomic-level polishing slurry for TC4 titanium alloy according to claim 1, characterized in that, The oxidant is any one of hydrogen peroxide, sodium hypochlorite, and potassium permanganate.

4. The atomic level polishing solution for TC4 titanium alloy according to claim 1, characterized in that, The complexing agent is any one of tartaric acid, phytic acid, and sorbic acid.

5. The atomic level polishing solution for TC4 titanium alloy according to claim 1, characterized in that, The pH of the polishing solution is 5-6.

6. A preparation method of the atomic-level polishing solution for TC4 titanium alloy according to claim 1, characterized in that, Includes the following steps: S1: Add rare earth abrasive particles to deionized water at a mass ratio of 1:3~5 and stir ultrasonically to obtain abrasive particle suspension A; S2: Add the dispersant to deionized water at a mass ratio of 1:2~3 and stir ultrasonically to obtain dispersant solution B; S3: Add the complexing agent to deionized water at a mass ratio of 1:2~3 and stir ultrasonically to obtain complexing agent solution C; S4: Add the dispersant solution B and the complexing agent solution C to the abrasive suspension A in sequence, and stir ultrasonically to obtain a mixture D; S5: Dissolve the oxidant in deionized water at a mass ratio of 1:3~5 to obtain oxidant solution E, and slowly add the oxidant solution E to the mixture D, and stir ultrasonically to obtain mixture F; S6: Add the pH adjuster to the mixture F, stir ultrasonically, and adjust the pH of the system to 5-6 to obtain the premix G; S7: Add deionized water to the premixed solution G to the set total amount, and stir ultrasonically to obtain the atomic-level polishing solution for TC4 titanium alloy.

7. The preparation method of the atomic-level polishing solution for TC4 titanium alloy according to claim 6, characterized in that, The ultrasonic stirring time in S1-S7 is 30~60 min, the ultrasonic frequency is 20~60 kHz, and the stirring speed is 200~600 rpm.

8. A polishing process of TC4 titanium alloy, characterized in that, The surface of a TC4 titanium alloy workpiece is polished using the atomic-level polishing fluid described in claim 1.

9. The polishing process of TC4 titanium alloy according to claim 8, characterized in that, The polishing process involves a polishing pressure of 20-30 kPa, a polishing disc rotation speed of 50-80 rpm, a polishing fluid flow rate of 10-20 mL / min, and a polishing time of 30-60 min.

10. The polishing process of TC4 titanium alloy according to claim 8, characterized in that, After polishing, the surface roughness Sa of TC4 titanium alloy is less than 0.2 nm, and the material removal rate is greater than 280 nm / min.